Swine as an animal model of cardiopulmonary resuscitation - LELOVAS (Π. ΛΕΛΟΒΑΣ), P.; MARINOU (Κ. ΜΑΡΙΝΟΥ), K.; XANTHOS (Θ. ΞΑΝΘΟΣ), Th.; PAPADIMITRIOU (Δ. ΠΑΠΑΔΗΜΗΤΡΙΟΥ), D.; PERREA (Δ. ΠΕΡΡΕΑ), D.; DONTAS (Ι. ΔΟΝΤΑ), I. (Journal of the Hellenic Veterinary Medical Society, 2017)
This paper reviews the advantages of swine in relation to other animal models of cardiopulmonary resuscitation referred to in the literature. The causes of cardiac arrest and the difficulties raised during research in humans are presented. All animal models used in this particular field are discussed and a detailed review is performed regarding the major anatomical and physiological similarities between swine and man, as well as the experimental studies published in the international literature.